2014
DOI: 10.18632/oncotarget.2338
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the obscurin-RhoGEF downregulates RhoA signaling and increases microtentacle formation and attachment of breast epithelial cells

Abstract: Obscurins are RhoGEF-containing proteins whose downregulation has been implicated in the development and progression of breast cancer. Herein, we aim to elucidate the mechanism for increased motility of obscurin-deficient cells. We show that shRNA-mediated obscurin downregulation in MCF10A cells leads to >50% reduction in RhoA activity relative to scramble control (shCtrl), as well as decreased phosphorylation of RhoA effectors, including myosin light chain phosphatase, myosin light chain, lim kinase, and cofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 54 publications
3
28
0
Order By: Relevance
“…These findings are critical for the development of individualized chemotherapies, since obscurin-deficient breast cancer patients may substantially benefit from a targeted therapy in the form of a PI3K inhibitor rather than a generalized chemotherapy, such as the taxanes. In line with this, our earlier studies have shown that obscurin-knockdown MCF10A cells display significantly increased survival and (re)attachment capabilities in the presence of paclitaxel compared to control cells expressing scramble shRNA [10]. Thus, the single or combinatorial use of PI3K inhibitors, such as the BKM120 used in our study, which is currently in clinical trials for several types of cancer including breast cancer, would potentially be a more appropriate and effective chemotherapy for treating obscurin-deficient breast tumors.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…These findings are critical for the development of individualized chemotherapies, since obscurin-deficient breast cancer patients may substantially benefit from a targeted therapy in the form of a PI3K inhibitor rather than a generalized chemotherapy, such as the taxanes. In line with this, our earlier studies have shown that obscurin-knockdown MCF10A cells display significantly increased survival and (re)attachment capabilities in the presence of paclitaxel compared to control cells expressing scramble shRNA [10]. Thus, the single or combinatorial use of PI3K inhibitors, such as the BKM120 used in our study, which is currently in clinical trials for several types of cancer including breast cancer, would potentially be a more appropriate and effective chemotherapy for treating obscurin-deficient breast tumors.…”
Section: Discussionsupporting
confidence: 54%
“…Specifically, breast cancer biopsies of grade-2 or higher exhibit dramatically reduced levels of giant obscurins, while residual proteins concentrate in large cytoplasmic puncta [9]. Obscurin-depleted non-tumorigenic breast epithelial MCF10A cells exhibit a growth advantage under anchorage-independent conditions, form mammospheres enriched with markers of stemness, extend microtentacles, and undergo epithelial to mesenchymal transition (EMT) resulting in disruption of adherens junctions, and enhanced motility and invasion in vitro [9, 10]. Consistent with these major alterations, depletion of giant obscurins from MCF10A cells expressing an active form of the K-Ras oncogene results in primary and metastatic tumor formation in subcutaneous and lung metastasis in vivo models, respectively [9].…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of giant obscurins from non-tumorigenic MCF10A breast epithelial cells promotes apoptotic resistance [ 10 ], disrupts adherens junctions, increases cell migration and invasion in vitro , and potentiates tumorigenicity and metastasis in vivo [ 12 ]. These alterations are attributed to the critical role of obscurins in cell cytoskeletal organization and dynamics [ 11 , 12 , 26 ]. The cell cytoskeleton is largely regulated by the family of RhoGTPases, including RhoA, which has been implicated in the regulation of cell mechanosensitivity in microenvironments of varying stiffness [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Rho GTPases RhoA, ras-related C3 botulinum toxin substrate 1 (Rac1) and cell division cycle 42 (Cdc42) are small molecular switches that contribute to the control of cell morphology and motility (5). RhoA is known to regulate actomyosin-based contractility and retraction through the Rho-kinase pathway, and is also associated with cell apoptosis and proliferation (6). Previous reports have observed that RhoA is localized to the plasma membrane microdomains, caveolae, in cardiomyocytes and endothelial cells (7).…”
Section: Introductionmentioning
confidence: 99%